2020
DOI: 10.1111/eip.13042
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of negative symptom severity with cognitive symptoms and functioning in subjects at ultra‐high risk for psychosis

Abstract: Aim: Negative symptoms and cognition are related with functioning in schizophrenia. However, it is not clear whether they have a similar effect in individuals at ultra-high risk (UHR) for psychosis. In this study, we aimed to explore relationship of negative symptoms with cognition and functioning cross-sectionally in people with UHR for psychosis.Methods: In total, 107 people participated in this study. We assessed negative symptoms with Scale for Negative Symptoms (SANS). We applied a cognitive battery inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Relative to expressive deficits, motivation and pleasure deficits are linked to worse outcomes in schizophrenia, including poorer occupational attainment ( Llerena et al, 2018 ) and quality of life ( Savill et al, 2016 ). Motivation and pleasure deficits also better predict real-life functioning and quality of life among individuals at clinical high-risk for psychosis (CHR) ( Glenthøj et al, 2020 ; Üçok et al, 2021 ). Despite their profound functional impact, there are no established treatments for motivation and pleasure deficits in schizophrenia ( Kirkpatrick et al, 2006 ; Galderisi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relative to expressive deficits, motivation and pleasure deficits are linked to worse outcomes in schizophrenia, including poorer occupational attainment ( Llerena et al, 2018 ) and quality of life ( Savill et al, 2016 ). Motivation and pleasure deficits also better predict real-life functioning and quality of life among individuals at clinical high-risk for psychosis (CHR) ( Glenthøj et al, 2020 ; Üçok et al, 2021 ). Despite their profound functional impact, there are no established treatments for motivation and pleasure deficits in schizophrenia ( Kirkpatrick et al, 2006 ; Galderisi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the independence of cognitive deficits from positive symptoms has been shown previously ( Green, 1996 ; Mohamed et al, 1999 ; Hughes et al, 2003 ; Gladsjo et al, 2004 ; Wagner et al, 2005 ; Keefe et al, 2006 ). On the other hand, a relationship between negative symptom severity and cognitive performance has been observed ( Mohamed et al, 1999 ; Gladsjo et al, 2004 ; Keefe et al, 2006 ; Üçok et al, 2020 ). Furthermore, improvements in negative symptoms have been found to be associated with amelioration of cognitive deficits in people with schizophrenia treated with olanzapine or AMI for eight weeks ( Wagner et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have now examined PNS in this population in relation to functioning and neurocognitive capacity and one report described a significant difference in verbal fluency between clinical high risk individuals with and without PNS (Yung et al, 2019); although no such differences were observed in another recent and large longitudinal study (Devoe et al, 2020). Finally, another recent study (Ucok et al, 2020) found that negative symptoms had an impact on functioning in a cohort of clinical high risk.…”
Section: Discussionmentioning
confidence: 99%